Optimal inflation-growth threshold: A case of the WAMZ member states - Olorunsola E. Olowofeso; Maimuna John-Sowe; Adegoke I. Adeleke; Santigie M. Kargbo; Joseph R. Yengbe; Yaya Cham (West African Monetary Institute (WAMI), 2023)
This study provides country-specific empirical evidence on the optimal inflation-growth threshold in the WAMZ over the period 1996-2021. Although there is large empirical literature on this subject, however, previous studies on the WAMZ economies generally focused on exogenous approaches of determining optimal inflation which impose a sharp and most often linear behaviour on the threshold level of inflation. This paper contributes to the policy debate on the inflationgrowth nexus by endogenously determining the individual country inflation threshold for six WAMZ countries. The results from the study show optimal inflation rates of 10.2 percent for Ghana, 10.8 percent for Guinea, 8.7 percent for Liberia, 10.8 percent for Nigeria and 7.4 percent for Sierra Leone, at 5 percent significant level. The Gambia, however, has 6.6 percent inflation threshold but was found statistically insignificant and thus, inconclusive. Also, most of the countries in the WAMZ have inflation in the low regime to be positive and statistically significant while the high inflation regime is strongly negative, suggesting adverse effects of high inflation on growth. This finding is consistent with the theoretical proposition. It is remarkable to note that inflation threshold for the three "relatively large" economies (Nigeria, Ghana, and Guinea) in the WAMZ hovers around 10.0 percent, in line with initial WAMZ inflation convergence criteria (10 percent) as well as WAMI (2022) study of 10.3 percent. The relatively lower inflation thresholds for The Gambia, Liberia, and Sierra Leone suggests a potential difference in inflation tolerance levels relative to the size of the economies. Overall, the findings provide strong empirical support for the policy stance of WAMZ convergence criterion to contain inflation to an "upper" singledigit level. Thus, Central Banks are encouraged to continue to pursue appropriate monetary policy measures to lower inflation to the desirable single-digit level.
Keywords: E31; O47; C22; 330; Inflation; Growth; Threshold Effects; Smooth Transition Regression; West Africa